Healthcare resource utilization and costs in patients with newly diagnosed acute myeloid leukemia. (2nd November 2018) - Hagiwara, May; Sharma, Arati; Chung, Karen C.; Delea, Thomas E.
Abstract: Aim: Acute myeloid leukemia (AML) is associated with high disease burden. This analysis estimated HRU and costs among newly diagnosed AML patients in a US commercially insured population. Materials and methods: This was a retrospective observational study using the IMS Health PharMetrics Plus and Hospital Charge Detail Master databases. Patients included adults who were newly diagnosed with AML between January 2007 and June 2016 ("study period"). Patients with <12 months of continuous enrollment prior to the index date were excluded, as were those whose first diagnosis was AML in remission/relapse, those diagnosed with acute promyelocytic leukemia, those on Medicare supplemental insurance, or those with a diagnosis of AML in remission/relapse without evidence of treatment during the study period. Patients were stratified by receipt of AML treatment (chemotherapy/hematopoietic cell transplantation [HCT]), and their follow-up was partitioned into initial, remission, and relapsed health states. Mean HRU and costs were tallied by treatment and, for treated patients, by health state and time since entry into health state (≤6 vs >6 months). Results: A total of 9, 455 patients met study criteria, including 6, 415 (68%) treated and 3, 040 (32%) untreated patients, with mean follow-up of 18.3 and 16.4 months, respectively. Mean age was 55 years in treated patients and 60 years in untreated patients. Mean total costs per patient were 386, 077 in treated patients and 79, 382 in untreated patients. For treated patients, 60% of total costs (231, 867 per patient) were incurred during the initial health state, representing time without remission/relapse. Mean monthly total healthcare costs were 21, 055 and 4, 854 among treated and untreated patients, respectively. Limitations and conclusions: HRU and costs of managing AML patients are substantial. In treated patients, the majority of costs were incurred during the initial treatment period, without claims indicating remission/relapse.